RESPON JARAK TANAM DAN DOSIS UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata. Sturt) - Tangguh Prakoso; Luqman Khakim (Fakultas Pertanian, Universitas Janabadra, 2024)
Sweet corn is a vegetable commodity that is very popular in America, Canada and Asia, including Indonesia, where sweet corn has become known since the 1980s. The volume of sweet corn imports in Indonesia in 2021 increased by 15%, with total imports reaching 995.99 thousand tons. Market demand for sweet corn continues to increase, reaching 11.1 million tons for food industry raw materials, 5.93 million tons for food industry raw materials, 405 thousand tons for household consumption, and around 1.5 million tons for other needs. However, this has not been able to meet the large demand required. Low corn productivity can be caused by several factors, such as not yet implementing recommended cultivation technologies such as setting plant spacing and urea fertilizer doses. This research used a factorial Randomized Complete Block Design (RCBD) method with two factors, namely planting distance (J) with 3 levels, namely J0: 70 cm x 10 cm with a total of 72 plants per plot, J1: 70 cm x 25 cm (control) with 28 plants per plot, J2: 70 cm x 40cm with 16 plants per plot. The second factor is the dose of urea fertilizer (D) with 3 levels, namely: D0: 200 kg/ha with a fertilizer dose of 126 g/plot, D1: 350 kg/ha (control) with a fertilizer dose of 220 g/plot, and D2: 500 kg/ha with a fertilizer dose of 315 g/plot. The results showed that increasing plant spacing and higher urea fertilization had an effect on increasing the growth and yield of sweet corn plants.